ACRL:n informaatiolukutaidon kehykset korkeakoulukirjastoissa Suomessa ja Yhdysvalloissa - Syvälahti, Kati; Asplund, Janika (Informaatiotutkimus, 2018)
This article discusses the international IL framework in the Finnish academic library context. In our online questionnaire conducted in May 2017, we researched how Finnish academic libraries in the universities and universities of applied sciences have received the Information literacy framework launched by The ACRL (Association of College and Research Libraries) in 2015. In the article, we discuss the current awareness of the frames in Finland and show practical examples of using the frames. The usefulness as well as the pros and cons of the frames are being analyzed. This article compares the current interpretation of the frames in Finland with the recent discussion in the academic libraries in the United States. Moreover, we address the transition from the IL standards to the Information literacy framework, and discuss similarities in the themes discussed in the States and Finland. Our conclusion was that in Finland, the majority of the libraries are aware of the IL frames and some of the libraries have already used the framework in developing information literacy in higher education.